Synonyms in the Turkish language - Қaлиев, A. Қ.; Қортaбaевa, Г. Қ. (Journal of Oriental Studies, 2017)
Synonyms appeared in the Turkish language and the large variety of ways. Often next to the old Turkish word, a new, heard and adopted from foreign neighbors. The new word could not eliminate the old, has taken root in the speech. It could not completely replace it, and lisch pushed into the other position. The article gives a brief overview on synonyms of the Turkish language.